ANALISIS HUBUNGAN PENGARUH GAYA HIDUP HEDONISME, PENDIDIKAN KEUANGAN DI KELUARGA DAN LITERASI KEUANGAN TERHADAP MANAJEMEN KEUANGAN PRIBADI - Wismar`ein, Dian; Aji Saputra, Nelwan (Universitas Muria Kudus, 2023)
This study aims to examine the effect of a hedonistic lifestyle, Family financial education, and financial literacy on the personal financial management of students in the Faculty of Economics and Business Universitas Muria Kudus majoring in financial management. This study proposed independent variables, namely hedonism lifestyle, financial education in the family and financial literacy. The dependent variable in this study is personal financial management. This study uses a quantitative method. The student at Universitas Muria Kudus majoring in financial management becomes our research object. SPSS version 25 is used to analyze the data Analysis of the instruments used for the validity and reliability tests. This study conducted the normality test, multicollinearity test, heteroscedasticity test, regression analysis, t-test, f-test, and coefficient of determination (Adjusted R2) to analyze the data. The results showed that: (1) there was a negative and significant effect of a hedonistic lifestyle on personal financial management, (2) there was a positive and significant effect of financial education in the family on personal financial management, (3) there was a positive and significant influence of financial literacy on management. Personal finance, (4) there is a positive and significant effect of hedonism lifestyle, financial education in the family and financial literacy on personal financial management